KONSEP KEADILAN DALAM PEMANFAATAN HASIL DESTINASI WISATA KEARIFAN LOKAL DITINJAU DARI PERSPEKTIF HAK ASASI MANUSIA (KECAMATAN BANDONGAN MAGELANG) - Abqa, Muhammad Ardhi Razaq; Kurniasih, Yuni; Hakim, Sholihul (Universitas Stikubank, 2024)
It is important to conduct research on the concept of justice in the utilization of the results of local wisdom tourism destinations from the perspective of human rights (Bandongan District, Magelang). This is to analyze the main problem formulation: (1) how is the concept of justice in the utilization of local wisdom tourism destinations in Bandongan Sub-district? (2) how is the influence of human rights values in the policy of utilization of local wisdom tourism destinations in Bandongan Sub-district? Data collection in this study was conducted through the collection of legal materials, observation, in-depth interviews, and FGDs with key groups. The data collected was then processed and analyzed to produce an analytical description to answer the questions raised in the research. The results showed that the tourism village is committed to achieving a comprehensive understanding of justice. This understanding includes various fundamental aspects, such as social, political, economic, legal, and cultural. Then the values of human rights also influence the policy of utilizing the results of tourist destinations, namely the community is given equality to provide aspirations in tourist destination policies, provide protection and respect for customs, regional musical instruments, rituals, dialects, and local wisdom, given equal opportunities for entrepreneurship, fulfilled conservation of the natural environment, given social development without discrimination. Keywords: Concept of Justice, Tourism Destination Outcomes, Local Wisdom, Human Rights.